Deviant Status: Stigmatized Women in Early Christianity - Menéndez Antuña, Luis (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2018)
Pastoral letters are composed in a polemical context. The polemic inside the community between the official doctrine and that of the opponents reflects a struggle for power between two groups who pretend to establish normative organization models. The present study pretends to show the dynamics by which the author tries to make illegitimate the opponent’s position and bar them from the community. At the same time, the Letters show how some women took part actively in opponent’s movement and claimed for authority and protagonism. The aim of the article is to study women’s status inside the community and analyse the normative proposals both groups designed for them.
Keywords: Pastoral Epistles; Primitive Church; women; power; status